2013
DOI: 10.1371/journal.pone.0054595
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of AKT Anti-Apoptotic Signaling by a Novel Drug Candidate Results in Growth Arrest and Apoptosis of Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma (HCC) is the third most common cause of cancer fatalities worldwide, with limited treatment options and five year survival rates of between <5 and 15%. To address this medical need, we conducted a screen of a drug-like small molecule library for HCC-selective cytotoxins. We report here the identification of a disubstituted aminothiazole termed HBF-0079, with remarkable selective toxicity for HCC-derived cell lines versus non-HCC liver lines and most other cancer lines. HBF-0079 caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…PI-3K/Akt signaling in human HepG2 hepatoma cells plays a key role in basal cell proliferation that correlates with increased cyclin D1 (55), and in insulin growth factor receptor-mediated DNA replication (55). Small molecules that abrogate Akt phosphorylation in human HCC cell lines caused irreversible growth arrest and apoptosis (56), indicating the importance of Akt-mediated signaling for the growth and survival of transformed cells within liver tumors. In the present study, APO10LA significantly reduced hepatic surface tumor volume by 65% (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…PI-3K/Akt signaling in human HepG2 hepatoma cells plays a key role in basal cell proliferation that correlates with increased cyclin D1 (55), and in insulin growth factor receptor-mediated DNA replication (55). Small molecules that abrogate Akt phosphorylation in human HCC cell lines caused irreversible growth arrest and apoptosis (56), indicating the importance of Akt-mediated signaling for the growth and survival of transformed cells within liver tumors. In the present study, APO10LA significantly reduced hepatic surface tumor volume by 65% (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signalling pathway is related to HCC cell proliferation 16 . Previous reports have shown that ARRB1 mediates Akt phosphorylation to activate PI3K/Akt signalling in response to a variety of stimuli 28 .…”
Section: Arrb1 Deficiency Suppresses Hepatocellular Carcinogenesismentioning
confidence: 99%
“…Akt is frequently induced in human HCC samples, and overexpression of Akt in mouse livers results in tumour development 14,15 . Disruption of the PI3K/Akt axis correlates with HCC growth arrest and/or apoptosis 16 . The mechanism of TNF-a-induced Akt activation in HCC is still unclear, and the interaction between TNF-a and Akt in HCC needs to be further investigated A family of seven-transmembrane domain G-protein-coupled receptors (GPCRs) constitutes the largest known superfamily for signal transduction and transmission 17 .…”
mentioning
confidence: 99%
“…There are only a handful of small molecules that have been reported to possess selective toxicity to liver cancer versus normal liver cells, making the aminothiazoles described here unusual. 1319 Moreover, none of the other liver cancer-selective small molecules have been further progressed, to our knowledge. These compounds are mainly phenolic or flavonoid natural products which were isolated from herbs.…”
mentioning
confidence: 99%